MA‐XRF investigation of the Altenberg Retable from 1330. (22nd January 2018) - Hoffmann, P.; Flege, S.; Ensinger, W.; Wolf, F.; Weber, C.; Seeberg, S.; Sander, J.; Schultz, J.; Krekel, C.; Tagle, R.; Wittkopp, A.
Abstract : The Altenberg Retable is one of the most important works of German art from the early 14th century. Composed of a shrine, a Madonna figure, and painted wings, it once adorned the high altar of the convent church in Altenberg/Lahn. The side and rear walls of the shrine were overpainted in 1609. Although conventional methods such as infrared reflectography and X‐ray radiography could not reveal the underlying medieval paint layer, we succeeded by conducting μ‐X‐Ray fluorescent studies. The latter measurements included a handheld spectrometer as well as μ‐X‐Ray fluorescent large area scanner. Nine sections of the side and rear walls were examined as well as a field on one of the wings (as a reference). In each section, spectra were recorded that comprised about 20 elements ranging from K to Bi. Maps of Ca, Fe, Co, Cu, Zn, As, Hg, and Pb were evaluated and interpreted on the basis of the results of prior color sampling analysis. By superposing several element maps, the original medieval iconographic program with its rows of standing saints could be revealed. With the help of iconographic comparison, these saints could be identified: St. Christopher in the central part of the rear wall, flanked by the 4 female saints Clare, Agnes, Dorothy, and Barbara. On the side walls, the apostles Peter and Paul, as well as the deacons Stephen and Lawrence were depicted. Discussed are not only different scenarios of usage for these images behind the altar but also the limits and possibilities of the measurement technology in this specific application.